Impact of adolescent stress on the expression of stress-related receptors in the hippocampus of animals exposed to alcohol prenatally - Raineki, Charlis (Hippocampus, 2018)
Many functions of the hippocampus are affected by prenatal alcohol exposure (PAE). In particular, dysregulation of the stress response is especially important because individuals with PAE carry increased risks for exposure to stressful environments throughout life. Little is known, though, about how adolescent stress in the context of PAE-related stress system dysregulation may further alter hippocampal development. Here we investigate the short- and long-term effects of adolescent chronic mild stress (CMS) on mRNA expression of stress-related mineralocorticoid (MR), glucocorticoid (GR), and type 1 CRH (CRHR1) receptors in the dorsal and ventral hippocampal formation of PAE and control rats. Our results indicate that PAE affects the expression of stress-related receptors in the hippocampus; however, PAE effects were more prominent during adolescence, as MR and CRHR1 mRNA expression were altered in both male and female PAE animals, with GR mRNA expression alterations observed only in PAE female. In adulthood, the effects of PAE were restricted to alterations in CRHR1 mRNA expression in females, while there were no effects in males. In contrast, the effects of adolescent CMS were more pronounced in adulthood, long after stress exposure termination. Importantly, PAE animals were less responsive to adolescent CMS, with effects only on CRHR1 in PAE animals compared to the altered MR, GR and CRHR1 mRNA expression observed in controls. Together, our results show that PAE and adolescent CMS induce dynamic alterations in the expression of stress-related receptors in the hippocampal formation that manifest differently depending on the age and sex of the animal.